2018
DOI: 10.1111/nep.12995
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on low‐molecular weight heparin infusion as anticoagulation for nocturnal home haemodialysis

Abstract: Low-molecular weight heparin infusion is practical and effective as anticoagulation for NHHD. It can be safely used in an alternate-day haemodialysis schedule. A close monitoring for LMWH accumulation is recommended if long dialysis is performed daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The anticoagulation performance of this regimen was first compared to that of the single‐bolus injection of nadroparin in 4‐h haemodialysis treatments . Then the performance of this regimen was compared to that of UFH infusion in extended 8‐h haemodialyses . In both of these trials, serial blood samplings for paired APTT and anti‐Xa activity at scheduled intervals after nadroparin administration were performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anticoagulation performance of this regimen was first compared to that of the single‐bolus injection of nadroparin in 4‐h haemodialysis treatments . Then the performance of this regimen was compared to that of UFH infusion in extended 8‐h haemodialyses . In both of these trials, serial blood samplings for paired APTT and anti‐Xa activity at scheduled intervals after nadroparin administration were performed.…”
Section: Methodsmentioning
confidence: 99%
“…2 Then the performance of this regimen was compared to that of UFH infusion in extended 8-h haemodialyses. 3 In both of these trials, serial blood samplings for paired APTT and anti-Xa activity at scheduled intervals after nadroparin administration were performed. Both trials were approved by the institutional ethics committee and written informed consents were obtained from the participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A loading dose followed by a continuous infusion throughout the HD treatment is preferred as repeated intermittent dosing is usually not practical, particularly for nocturnal dialysis. Study on use of continuous infusion of LMWH in home HD has also been published …”
Section: Home Hdmentioning
confidence: 99%
“…Study on use of continuous infusion of LMWH in home HD has also been published. 140 Mass balance studies in patients having long-hour dialysis found that the use of a dialysate calcium level of 1.25 mmol/L associates with a fall in pre-dialysis calcium level as well as increases in alkaline phosphatase and intact parathyroid hormone levels. Such abnormalities could be reversed by increasing the dialysate calcium level and hence, a dialysate calcium level of 1.5 mmol/L is suggested.…”
Section: Home Hdmentioning
confidence: 99%